The Routledge International Handbook of Posttraumatic Growth - Berger, Roni (Taylor & Francis, 2024)
The Routledge International Handbook of Posttraumatic Growth offers a rich covering of approaches to different traumatic and stressful experiences in relation to posttraumatic growth (PTG). This handbook explores benefits that individuals, couples, families, organizations and communities can experience following the struggle with highly stressful and potentially traumatic events. Split into seven parts and written by a diverse international team of multidisciplinary contributors who provide a comprehensive overview of PTG, topics include: religious and spiritual aspects of PTG, gender in PTG, PTG in LGBTQ+, perinatal bereavement, and more. The Routledge International Handbook of Posttraumatic Growth represents an essential resource for students, researchers and professionals, including social workers, psychologists, nurses, mental health counsellors and psychiatrists.